2021
DOI: 10.26740/jaj.v12n2.p193-203
|View full text |Cite
|
Sign up to set email alerts
|

Covid 19 Outbreak and Financial Statement Quality: Evidence from Central Java

Abstract: This study aims to analyze and find empirical evidence that the Covid 19 pandemic will affect the quality of financial reports and what factors affect the quality of government financial reports. The variables used in this study are competence, compliance with government accounting standards, external pressures, environmental uncertainty, internal control systems, and the quality of financial reports. The population of this study was accounting or finance staff who served in 48 SKPDs in the Central Java Provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…The results of this study support the previous research results which state that the use of IT has a positive and significant effect on the quality of financial reports (Cahyani, 2023;Kuntadi & Puspita, 2023;Prasetyo, 2015;Wahyuni et al, 2018). However, the results of this study are not in line with the results of similar research which empirically proves that the use of IT does not affect the quality of financial reports (Erin & Adegboye, 2021;Nurcahyono et al, 2021).…”
Section: Effect Of Utilization Of Ti On the Quality Of Financial Reportcontrasting
confidence: 53%
“…The results of this study support the previous research results which state that the use of IT has a positive and significant effect on the quality of financial reports (Cahyani, 2023;Kuntadi & Puspita, 2023;Prasetyo, 2015;Wahyuni et al, 2018). However, the results of this study are not in line with the results of similar research which empirically proves that the use of IT does not affect the quality of financial reports (Erin & Adegboye, 2021;Nurcahyono et al, 2021).…”
Section: Effect Of Utilization Of Ti On the Quality Of Financial Reportcontrasting
confidence: 53%
“…Thus, the second hypothesis is rejected. Financial stability is a condition that describes the company's financial condition as a stable condition (Jamil & Yudowati, 2019;Nurcahyono, Sukesti, et al, 2021;Permata et al, 2021). This test does not fit the agency's theory that financial stability negatively affects financial statement fraud.…”
Section: Effect Of Financial Stability On Financial Statement Fraudmentioning
confidence: 99%
“…The research results showed the reduced credibility of financial statements during the SARS-CoV-2 pandemic. Nurcahyono, Sukesti, and Alwiyah [71] studied whether the SARS-CoV-2 pandemic affected the quality of financial statements and what factors affected the quality of government financial statements. It was found that the pandemic affected this quality, with environmental uncertainty being the primary negative factor.…”
Section: The Relevance Of the Sars-cov-2 Pandemic Period For The Info...mentioning
confidence: 99%